CERRADOS: PELOS CAMPOS HÁ FOME - Lima, João Donizete (Caminhos de Geografia, 2001)
The project of national integration seeking the economical development, they broughtfor the area of the Brazilian savannah, besides the degradation of your ecosystem, socioeconomic contrasts. For the geo-environmental characteristics of the savannahs and for presenting disparities in the space occupation. A great need exists of motivating researches, looking for a better understanding of that ecosystem, to maintain the balance of the natural resources in way to contribute for a more rational human occupation.